Surveying theoretical approaches within digital religion studies. (January 2017) - Campbell, Heidi A
This article provides an overview of the development of Digital Religion studies and the theoretical approaches frequently employed within this area. Through considering the ways and theories of mediatization, mediation of meaning, and the religious–social shaping of technology have been engaged and applied in studies of new media technologies, religion, and digital culture we see how Digital Religion studies has grown into a unique area of inquiry informed by both Internet studies and media, religion, and culture studies. Overall, it offers a concise summary of the current state of research inquiry within Digital Religion studies.